2020
DOI: 10.1111/pai.13337
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association study reveals a novel locus for asthma with severe exacerbations in diverse populations

Abstract: Background: Severe asthma exacerbations are a major cause of asthma morbidity and increased healthcare costs. Several studies have shown racial and ethnic differences in asthma exacerbation rates. We aimed to identify genetic variants associated with severe exacerbations in two high-risk populations for asthma. Methods: A genome-wide association study of asthma in children and youth with severe exacerbations was performed in 1283 exacerbators and 2027 controls without asthma of Latino ancestry. Independent sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…The complete summary of the results is presented in Table S3. The asthma-associated variants in 2p21 near LDHAP3, a locus previously associated with severe asthma exacerbations in Latinos from GALA II [25], had a predominant effect in males and were nominally significant in the interaction and female-only analyses (p-value < 0.05) (Tables 3 and S3). However, variants upstream of LCORL at 4p15.31 had sex-specific involvement in male asthma susceptibility, being nominally significant in the interaction GWAS (p-value < 0.05), but not in females (p-value > 0.05) (Tables 3 and S3).…”
Section: Stratified Gwas In Femalesmentioning
confidence: 96%
See 1 more Smart Citation
“…The complete summary of the results is presented in Table S3. The asthma-associated variants in 2p21 near LDHAP3, a locus previously associated with severe asthma exacerbations in Latinos from GALA II [25], had a predominant effect in males and were nominally significant in the interaction and female-only analyses (p-value < 0.05) (Tables 3 and S3). However, variants upstream of LCORL at 4p15.31 had sex-specific involvement in male asthma susceptibility, being nominally significant in the interaction GWAS (p-value < 0.05), but not in females (p-value > 0.05) (Tables 3 and S3).…”
Section: Stratified Gwas In Femalesmentioning
confidence: 96%
“…Genotyping was carried out with the Axiom LAT1 array (817,810 genetic variants) and the Axiom LAT1 Array Plus HLA (812,715 SNPs) (Affymetrix), as described elsewhere [25], and joined quality control was carried out for the subset of 803,225 variants resulting from the intersection of the two arrays. Quality control main steps included the exclusion of individuals with: low call rate (<97%), a discrepancy between reported gender and biological sex, relatedness with other subjects (Pi-hat > 0.3), and evidence of being outliers for any of the three first principal components of the genotype matrix (>six standard deviations) estimated with PLINK 1.9 [47].…”
Section: Genotyping Imputation Of Genetic Variants and Ancestry Assessmentmentioning
confidence: 99%
“…It is well known that genetics is a strong determinant for the risk of developing asthma exacerbations, particularly in persons with African ancestry. The second highlighted article by Esther Herrera‐Luis et al investigated this risk by genome‐wide association studies in various populations, including African Americans and Hispanics/Latino children with severe asthma exacerbations, as well as controls 9 . The initial screening included over 3000 individuals of various ethnic origins.…”
mentioning
confidence: 99%
“…The second highlighted article by Esther Herrera-Luis et al investigated this risk by genome-wide association studies in various populations, including African Americans and Hispanics/Latino children with severe asthma exacerbations, as well as controls. 9 The initial screening included over 3000 individuals of various ethnic origins. The study identified a novel genome-wide significant association for severe asthma exacerbations on chromosome 2p21.…”
mentioning
confidence: 99%
“…Care of asthma exacerbations is a major clinical challenge to the physician, and this condition has been largely studied and reported in PAI 13,14 . Here, the authors used a genetic approach to explain possible treatment failures, as the prime role of genetics in asthma has been largely established earlier 15–17 …”
mentioning
confidence: 99%